LABORARTORY BRNO - Pospíšil, Tomáš (Vysoké učení technické v Brně. Fakulta architektury)
Programem návrhu se stala galerie moderního a nového mediálního umění společně s komunitním centrem sloužícím tvorbě projektů na pomezí vědy a umění. Jedná se o dvě samostatné budovy, jejichž forma je značně ovlivněna prostředím, ve kterém se nacházejí. Novodobá hradba ulice Koliště je umocněna slepými betonovými fasádami navržených budov, příslušnost k Cejlu značí uzavřenost, syrovost, komunitnost a především parter formovaný jako dvě atria s rozdílnou měrou intimity. Dominantou projektu se stal převýšený zlatý kubus skrývající hlavní prostory galerie. Je umístěn až za hradbou budov a díky své výšce shlíží na centrum města. Zbylé objemy jsou nižší a méně honosné — k ulici se otáčí zády a naopak do atrií se zcela otevírají prosklenými stěnami. Cílem projektu byla snaha extrahovat a ztvárnit určité aspekty místa a vytvořit prostředí příjemné pro uživatele.

The object of the proposal is a gallery of modern and new media art together with a community centre, which serves as a platform for creating projects in borderland between science and art. The form of the two separately standing buildings is significantly influenced by their surroundings. The modern barrier of the street Koliště is enhanced by blind concrete facades of the designed buildings. The unity with Cejl indicates reclusion, rawness and sense of community, especially significant is the parterre which is shaped as two atria with different levels of intimacy. The dominant feature of the project is a superelevated golden cube, which conceals the main space of the gallery. It is situated behind the wall of buildings and it looks down at the city centre, which is possible thanks to its height. The remaining space is located in lower level and it is less opulent, as it stands back to the street on one side and completely opens itself into atriums through glassed-in walls on the other side. The goal of the project was to extract and put into shape specific aspects of the place and to create a user-friendly environment.
LABORARTORY BRNO
Keywords: architektura; galerie; muzeum; hackerspaces; labs; blackbox; Cejl; Brno; nároží; surovost; nová média; komunitnost; architecture; gallery; museum; hackerspaces; labs; blackbox; Cejl; Brno; rawness; corner; new media; community